2011
DOI: 10.1002/marc.201100224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen Bonding on Intramolecular Chain Transfer in Polymerization of Acrylates

Abstract: Propagation rate coefficients (k(p) ) for 2-hydroxyethyl acrylate (HEA) have been determined by pulsed-laser polymerization (PLP) combined with size-exclusion chromatography (SEC) between 20 and 60 °C using pulse repetition rates of 50 and 100 Hz. The success of PLP-SEC under these conditions suggests that HEA is not subjected to the intramolecular chain transfer to polymer (backbiting) reactions dominant for other acrylates; (13) C NMR analysis shows that the quaternary carbon observed in PLP-generated poly(b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 51 publications
(122 reference statements)
5
48
1
Order By: Relevance
“…Firstly, from an experimental point of view, although the reaction was performed under conditions designed to minimize any effect arising from the exothermic nature of the reaction in bulk, local temperature rises are inevitable and can lead to increased rate of both backbiting and β scission relative to propagation. Secondly, as the solution polymerization is conducted in ethanol, hydrogen bonding may result in a decrease in the amount of backbiting relative to the bulk polymerization 41,42 . Finally, the potential of the midchain radical to undergo chain transfer to solvent for the reaction conducted in ethanol, which has not been considered herein, may also lead to a reduction in the products arising from the midchain radical as has been demonstrated to be important for reactions carried out in the presence high concentrations of chain transfer agent 55,56 .…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, from an experimental point of view, although the reaction was performed under conditions designed to minimize any effect arising from the exothermic nature of the reaction in bulk, local temperature rises are inevitable and can lead to increased rate of both backbiting and β scission relative to propagation. Secondly, as the solution polymerization is conducted in ethanol, hydrogen bonding may result in a decrease in the amount of backbiting relative to the bulk polymerization 41,42 . Finally, the potential of the midchain radical to undergo chain transfer to solvent for the reaction conducted in ethanol, which has not been considered herein, may also lead to a reduction in the products arising from the midchain radical as has been demonstrated to be important for reactions carried out in the presence high concentrations of chain transfer agent 55,56 .…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study,22 it was found that the PLP–SEC technique could be applied to determine k p values for the homopolymerization of HEA with a pulse repetition rate of 100 Hz under conditions at which other acrylates cannot be studied. It was concluded that intermolecular hydrogen bonding between HEA monomers significantly suppresses backbiting, a reaction that is the main cause of the loss of PLP structure in the resulting MMD.…”
Section: Resultsmentioning
confidence: 99%
“…HEA (96% purity, containing 200–650 ppm monomethyl ether hydroquinone as inhibitor), ST (99% purity, containing 10–15 ppm of 4‐tert‐butylcatechol), photoinitiator 2,2‐dimethoxy‐2‐phenylacetophenone (DMPA, 99% purity), and anhydrous dimethyl sulfoxide‐d6 (DMSO‐d6, containing 99.9% D) were all obtained from Sigma–Aldrich and used as received. Low‐ conversion polymerizations were conducted in a pulsed laser setup as described in the previous articles 20–22. Monomer mixtures in bulk with 5 mmol L −1 DMPA photoinitiator were added to a quartz cell and exposed to laser energy using a Spectra‐Physics Quanta‐Ray 100 Hz Nd:YAG producing a 355 nm laser pulse of duration 7–10 ns and energy of 1–10 mJ per pulse, with the output repetition rate controlled by a digital delay generator (DDG, Stanford Instruments).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation rate coefficients of hydrophilic monomers in hydrophobic solvents are often larger than those in hydrophilic solvents. 12,13 This makes SqRAFTwP more attractive and powerful because the amount of hydrophilic monomers can be reduced to a negligible level, i.e., the adsorbing layer will not be so thick.…”
mentioning
confidence: 99%